Fragmentation of Coastal Grasslands by Plantations and Spontaneous Spread of Invasive Pines in the Southern Pampa - Yezzi, Alejandra Lorena (2021)
Coastal dunes of the southern Buenos Aires province, in Argentina, are one of the last remnants of biodiversity in the southern Pampa unit, within the Rio de la Plata Grasslands. While the direct loss of grasslands due to the advance of cities and afforestation is conspicuous, the negative effects of the subdivision of the remaining environments on biodiversity and ecosystem dynamics are less considered. Our work aimed to analyze the combined effect of fires and subdivision of grasslands by invasive alien trees. Our results suggest that fragmentation affects the resilience of coastal grasslands after fire and affects the course of succession, promoting the establishment of invasive alien plants. We also suggest that fires favor the advance of pines and acacias towards the interior of grassland remnants, further reducing their area. The effective conservation of the components of Pampas biodiversity that still persist in these coastal ecosystems will depend on preventing, mitigating and compensating the insularization effects associated with forest plantations and the expansion of invasive trees, by means of adequate territorial planning that allows remnants to be maintained in a good state of conservation.